Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas X SMK Abdurrab Pekanbaru pada Materi SPtLDV - Astuti, Putri Puji; Siregar, Syarifah Nur; Murni, Atma (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematical problem solving ability is one of the mathematical abilities that students need to have. The purpose of this study is to analyze students' mathematical problem solving abilities in solving contextual problems on SPtLDV material through qualitative descriptive research. The data collection technique was carried out by testing mathematical problem solving abilities by giving two essay questions to the research subjects consisting of 4 male students and 25 female students of class X Medical Labor Engineering (TLM) 2 SMK Abdurrab Pekanbaru in the 2024/2025 academic year, who were identified as having difficulties in solving mathematical problems. Analysis of students' mathematical problem solving abilities was measured through indicators: understanding the problem, planning problem solving, implementing the problem solving plan, and interpreting the results obtained. The results of the analysis of students' mathematical problem-solving abilities show the number of students who successfully achieved the maximum score on questions number 1 and number 2 respectively as follows: indicators of understanding the problem were 79.31% and 75.86%, planning problem solving was 65.52% and 48.28%, implementing the problem solving plan was 51.72% and 24%, and interpreting the results obtained was 44.83% and 20.69%.